E-learning design for Chinese classifiers : reclassification of nouns for a novel approach - Gao, Helena Hong (2015)
Chinese classifiers are found to be a category that creates true challenges for second language learners of Chinese to grasp its meaning and use it easily. It is also found that even native speakers of Chinese may lose their competence in using classifiers appropriately after years of living in a non-Chinese speaking community. This paper presents a novel approach in the design of an e-learning tool for Chinese classifier learning and teaching. With this approach, Chinese noun categories are reclassified according to their associations with the types of classifiers. The design is based on both theoretical studies of Chinese classifiers and empirical studies of Chinese classifier acquisition by both children and adults. It allows users to use cognitive strategies to explore and learn with a bottom-up approach the associations of classifiers with nouns.